Sistem Informasi Geografis Pemetaan Objek Wisata Di Kabupaten Barru Berbasis Web - Ahmad; Marlina; Hasnawati; Masnur; Wahyu Artanugraha; Ahmad Ahmad (STEKOM PRESS, 2025)
Barru Regency tourism has a variety of tourist attractions, but information related to the location and potential of tourism has not been digitally integrated, making it difficult for tourists and the government to access data. This study aims to design and build a web-based Geographic Information System (GIS) that can map the location of tourist attractions in Barru Regency interactively, easily accessible, and equipped with supporting information in the form of descriptions, types of tourism, photos, and travel routes. The research method used is Research and Development (R&D) with the stages of tourist attraction surveys, interface design, feature development, and system testing. The results of the study are in the form of a website